Assessment of a novel cryoablation device for the endovascular treatment of cardiac tachyarrhythmias. (3rd May 2018) - Baust, John M; Robilotto, Anthony; Guerra, Peter; Snyder, Kristi K; Van Buskirk, Robert G; Dubuc, Marc; Baust, John G
Objectives: Cryoablation is an effective alternative treatment for cardiac arrhythmias offering shortened recovery and reduced side effects. As the use of cryoablation increases, the need for new devices and procedures has emerged. This has been driven by technological limitations including lengthy periods to generate a single lesion (3–5 min), uncertain transmurality, and differential efficacy. Furthermore, due to limited ablation capacity under high heat loads, cryo has had limited success in the treatment of ventricular arrhythmias. To this end, in this study we evaluated a new cryoablation catheter, ICEolate, for the targeted ablation of cardiac tissue. Methods: Performance assessment included calorimetry, freeze zone isothermal distribution characterization and catheter ablation capacity in a submerged, circulating, heat-loaded ex vivo tissue model. A pilot in vivo study was also conducted to assess ablative capacity of the cryocatheter in a fully beating heart. Results: Ex vivo studies demonstrated ice formation at the tip of a cryocatheter within 5 s and a tip temperature of ~−150°C within 10 s. The device repeatedly generated freeze zones of 2 cm × 3 cm in less than 2 min. Tissue model studies revealed the generation of a full thickness (5–10 mm) cryogenic lesion within 1 min with an opposite (transmural) surface temperature of <−60°C under a circulating 37°C heat load. Pilot in vivo studies demonstrated the delivery of an ablative "dose, " producing a continuous full thickness transmural linear lesion in <60 s at both atrial and ventricular sites. Conclusion: These studies suggest that the supercritical nitrogen cryodevice and ICEolate cryocatheter may provide for rapid, effective, controllable freezing of targeted tissue. The ablative power, speed, and directional freeze characteristics also offer the potential of improved safety via a reduction in procedural time compared to current cryoablation devices. These technological developments may open new avenues for the application of cryo to treat other cardiac arrhythmogenic disorders.